Managing for timber and biodiversity in the Congo Basin - Nasi, Robert; Billand, A.; Vliet, N. van (2011)
Multiple-use forest management is considered by many as a preferable alternative to single-use, generally timber-dominant, management models. In the Congo Basin rainforests, integration of timber and non-timber forest resources plays a key role in the subsistence and market economies of rural communities. This is however mainly occurring in “ordinary” forest lands and not in formally gazetted forest lands. In this paper we briefly explore the major land-uses in the Congo Basin and their actual or potential for multiple-use. We then focus on the most extant production system (industrial logging concessions) and analyze the existing issues and options for managing actively both timber and biodiversity with a special emphasis on wildlife and the role of certification. A few promising but yet ‘unfinished’ examples do exist in the region and we review these cases to draw lessons and recommendations. We contend however that true multiple-use could only be realized by expanding beyond boundaries of formal management units through new innovative land-use units, allowing a spatial cohabitation of the interests of local people, of conservation proponents and of extractive industries in the same management unit.